Banking crises and recessions: What can leading indicators tell us? - Matthew Corder; Martin Weale (Bank of England, External Monetary Policy Committee Unit, 2011)
It is widely suggested that there is some relationship between banking crises and recessions. We assess whether there is evidence for interdependency between recessions and banking crises using both non-parametric tests and unconditional bivariate probit models and find strong evidence for interdependence. We then consider whether leading indicators can help predict banking crises and recessions and if these variables can explain the previously observed interdependence. Inclusion of exogenous variables means that the observed interdependence between banking crises and recessions disappears - indicating that the observed interdependence is a result of easily observable common causes rather than unobserved links.
Keywords: E37; G21; 330; Crises; recessions; interdependency; bivariate probit analysis; Wirtschaftslage; Bankenkrise; Konjunktur; Probit-Modell